THE USE OF MUSEUM FOR CULTURAL DAKWAH PURPOSES - samsinas, samsinas (Hunafa: Jurnal Studia Islamika, 2020)
This paper discusses the museum as a means of cultural da’wah. There are 2 main problems namely; how to interest visitors to the museum as a cultural propaganda suggestion and how is the intention of the museum visitors as a means of cultural propaganda? This study uses quantitative research types with analysis of cultural anthropological research and the science of da'wah. To measure the progress of this cultural propaganda can be seen through the level of visitor interest in Islamic artifacts and the level of visitor visits. The method and sample conducted a survey of 25 visitors using a questionnaire. The results found that the level of interest on Islamic artifacts and culture that are influenced by Islam with intention of visiting visitors in the museum showed the interest and intentions of cultural da’wah because of intense communication according to the communication patterns or da’wa patterns prevailing in the museum where a person or group of people came, observed, studied and understood everything related to Islam and culture that has been influenced by Islam through artifacts in the Central Sulawesi Museum over and over again.